AATF and SMARCA2 are associated with thyroid volume in Hashimoto’s thyroiditis patients - Brčić, Luka; Barić, Ana; Benzon, Benjamin; Brekalo, Marko; Gračan, Sanda; Kaličanin, Dean; Škrabić, Veselin; Zemunik, Tatijana; Barbalić, Maja; Novak, Ivana; Pešutić Pisac, Valdi; Punda, Ante; et al. (Scientific reports, 2020)
Thyroid volume of Hashimoto’s thyroiditis (HT) patients varies in size over the course of disease and it may reflect changes in biological function of thyroid gland. Patients with subclinical hypothyroidism predominantly have increased thyroid volume whereas patients with more pronounced hypothyroidism have smaller thyroid volumes. Suggested mechanism for thyroid atrophy is thyrocyte death due to apoptosis. We performed the first genome-wide association study (GWAS) of thyroid volume in two groups of HT patients, depending on levothyroxine (LT4) therapy, and then meta-analysed across. Study included 345 HT patients in total and 6 007 322 common autosomal genetic variants. Underlying hypothesis was that genetic components that are involved in regulation of thyroid volume display their effect in specific pathophysiologic conditions of thyroid gland of HT patients. We additionally performed immunohistochemical analysis using thyroid tissues and analysed differences in expression levels of identified proteins and apoptotic marker between HT patients and controls. We found genome-wide significant association of two loci, both involved in apoptosis, with thyroid volume of HT patients: rs7212416 inside apoptosis-antagonizing transcription factor AATF (P = 8.95 × 10 −9 ) and rs10738556 near chromatin-remodeling SMARCA2 (P = 2.83 × 10 −8 ). In immunohistochemical analysis we observed that HT patients with homozygous AATF risk genotypes have decreased AATF expression (0.46-fold, P < 0.0001) and increased apoptosis (3.99-fold, P = 0.0001) in comparison to controls. HT patients with heterozygous SMARCA2 genotypes have decreased SMARCA2 expression, albeit without reaching statistical significance (1.07-fold, P = 0.5876), and significantly increased apoptosis (4.11-fold, P < 0.0001). By two lines of evidence we show that two highly plausible genetic loci, AATF and SMARCA2 , may be involved in determining the thyroid volume of HT patients. The results of our study significantly add to the current knowledge of disturbed biological mechanisms in thyroid gland of HT patients.